1997
DOI: 10.1055/s-2008-1064066
|View full text |Cite
|
Sign up to set email alerts
|

Normal Aging and Environmental Effects on Communication

Abstract: This article focuses on the role of communication in the successful adjustments and adaptations to normal aging by elders. It views communication as an essential tool for living safely and independently, for maintaining interests and a sense of purpose, for continuing important social and family relationships, and for exercising active control over quality of life and care. The discussion emphasizes the importance of physical and social environments to elders' communication efforts and suggests that an environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…, Cruice et al . , Lubinski and Welland , Nakrem et al . ) and the provision of consistent and quality care (Bennett et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…, Cruice et al . , Lubinski and Welland , Nakrem et al . ) and the provision of consistent and quality care (Bennett et al .…”
Section: Discussionmentioning
confidence: 99%
“…Observations from this study also revealed a continued dominance of task-focused communication consistent with previous studies (Carpiac-Claver and Levy-Storms 2007, Levy-Storms 2011, Savundranayagam 2014), a dominance of staff directing the communication exchange (Williams et al 2003), limited opportunity for residents to engage in meaningful interpersonal communication with staff, and a desire from residents for more opportunities for communication. Resident-staff communication is integral to resident psychosocial well-being and quality of life (Bennett et al 2014, Cruice et al 2000, Lubinski and Welland 1997, Nakrem et al 2011) and the provision of consistent and quality care (Bennett et al 2014, Bryan et al 2002, McGilton et al 2010. Change from policy level through to daily care is needed to assess and better document residents' communication needs and to prioritize communication management as an explicit care task in residential-aged care settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Older adults with communication disorders may be at particular risk for negative consequences since communication is central to the process of successfully adjusting and adapting to the aging process. The ability to communicate effectively is essential for living independently, pursuing personal goals and interests, performing social roles and functions, maintaining personal and familial relationships, making decisions, and exercising control over quality of life and care (Lubinski & Welland, 1997). Studies have shown that the conversational skills of normally aging older adults tend to remain well-preserved, even though the semantic content and syntactic structure of language use change over the life-course (Shadden, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Much has been written on the challenges for older people in coping with the physiological, anatomical and concomitant health changes that they face and how these changes impact on their sense of self and empowerment when negotiating meeting their needs in the world (Tennstedt 2000, O'Hanlon and Coleman 2004). Difficulties with verbal communication in older people could lead to communication breakdown that gives rise to misperception of their wishes, undiagnosed or uncontrolled health problems, financial insecurity or social isolation and thus negative consequences for well‐being (Lubinski and Welland 1997). More recently it has become incumbent on older people to manage their own health, finances and social interactions and proficient communication underpins the capacity to maintain this level of independence.…”
Section: Introductionmentioning
confidence: 99%